Effects of WTO membership on income distribution and labour movement in China: A CGE analysis - Jiao Wang; David Mayes; Guanghua Wan (Bank of Finland, Institute for Economies in Transition (BOFIT), 2005)
Using a CGE model (PRCGEM) updated to 2002, the paper explores how WTO membership could affect earnings in 40 industries across 31 regions (and 8 regional blocks) of China during the period 2002 2007.Taking into account labour movement between regions within China, the direct contribution of WTO membership to overall economic growth and development is predicted to be small, with a rise in real GDP of only 6.48% short term and 5.6% long term. However, structural economic change and the WTO shock should increase regional output, especially in the established coastal economies.Regional labour movement is found to increase 69.2% at the completion of economic structural reforms.A slight decrease in the Gini coefficient for income inequality is also anticipated.
URN:NBN:fi:bof-201408072011
Keywords: C68; O18; R12; R23; 330; Applied CGE modelling; China; WTO; labour movement; inequality